Argon–seeded detachment during ELM control by RMPs in KSTAR. (1st April 2023) - Shin, H.; Hwang, J.; Han, Y.; Shin, G.; Lee, H.; Chai, K.-B.; Choe, Wonho
Abstract: In this study, we demonstrate argon-seeded discharges that exhibited a detached divertor during the full suppression and mitigation of edge-localized modes (ELMs) by an International Thermonuclear Experimental Reactor-like, three-row resonant magnetic perturbation (RMP) configuration in KSTAR. During the ELM suppression phase, the peak heat flux on the divertor target was successfully reduced from 1.6 MW m −2 –0.5 MW m −2 via argon seeding. Further, the ion saturation current densities corresponding to the particle fluxes on both targets were reduced by more than 50%. During the RMP grassy-ELM regime, a further reduction to 0.1 MW m −2 in the divertor heat load was successfully achieved. A highly localized radiation zone near the X -point was also observed during divertor detachment. The calculated degree of detachment based on the two-point model increased to levels of approximately 3 and 2.3 for the outer target and inner target cases, respectively. These results provide valuable information regarding the effect of mid- Z impurities on RMP-detachment-compatible discharges.